Influence of Managerial Ownership on Manager’s Earnings Management Preference when They Pursue Higher Bonus - JIA, SHUQI (2017)
Management bonus compensation is a common method used to alleviate agency problem. However, because of the “economic man” hypothesis and incompleteness of compensation contracts, managers are likely to sacrifice firm’s interests and owner’s interests in order to obtain a higher bonus. Earnings management (EM) is frequently-used by managers for this purpose. Except compensation incentive, managerial ownership is another way to reduce agency cost. But how it affects a manager’s EM preference when they manipulate earnings in order to acquire a higher bonus? This research paper presents and tests how managerial ownership affects manager’s earnings management preference when they manage earnings due to a bonus plan. In this research, the EM preferences analysed are the most practiced manipulation techniques, Accruals earnings management(ACC) and Real Earnings Management(REM). They all have different characteristics. Accruals earnings management is easy to be detected but it does not harm a firm’s future. Inversely, Real earnings management will damage a firm’s interest but it is less likely to draw auditors and regulators. Because of their different features, managers have different preferences when faced with different scenarios. Managerial ownership can be a reason of changing EM ways. On the one hand, because managers hold shares in the firm, they need to think more about the company’s long-term benefits, rather than considering solely personal interest within the term of contract. Thus, a close connection between a manager's interests and a firm’s value facilitate managers using Accruals earnings management. On the other hand, it makes managers also play a role like owners, giving them more power, especially in aspects such as choosing accounting policy and accounting performance recognition, which makes it convenient for them to manipulate earnings. Therefore, this is also a reason to use Accruals earnings management. Inversely, if there is no managerial ownership, managers do not consider whether Real earnings management will harm a firm’s future value and because they have less power, they are likely to choose Real earnings management. As a result, managerial ownership may affect manager’s preference of EM.